Yohimbine as a Starting Point to Access Diverse Natural Product-Like Agents with Re-programmed Activities against Cancer-Relevant GPCR Targets. Issue 14 (15th July 2020) - Paciaroni, Nicholas G.; Norwood, Verrill M.; Ratnayake, Ranjala; Luesch, Hendrik; Huigens, Robert W.
Graphical abstract: Abstract: G protein-coupled receptors (GPCRs) constitute the largest protein superfamily in the human genome. GPCRs play key roles in mediating a wide variety of physiological events including proliferation and cancer metastasis. Given the major roles that GPCRs play in mediating cancer growth, they present promising targets for small molecule therapeutics. One of the principal goals of our lab is to identify complex natural products (NPs) suitable for ring distortion, or the dramatic altering of the inherently complex architectures of NPs, to rapidly generate an array of compounds with diverse molecular skeletal systems. The overarching goal of our ring distortion approach is to re-program the biological activity of select natural products and identify new compounds of importance to the treatment of disease, such as cancer. Described herein are the results from biological screens of diverse small molecules derived from the indole alkaloid yohimbine against a panel of GPCRs involved in various diseases. Several analogues displayed highly differential antagonistic activities across the GPCRs tested. We highlight the re-programmed profile of one analogue, Y7g, which exhibited selective antagonistic activities against AVPR2 (IC50 = 459 nM) and OXTR (IC50 = 1.16 µM). The activity profile of Y7g could correlate its HIF-dependent anti-cancer activity to its GPCR antagonism since these receptors are known to be upregulated in hypoxic cellular environments. Our findings demonstrate that the ring distortion of yohimbine can lead to the identification of new compounds capable of interacting with distinct cancer-relevant targets.